A polypyrrole hollow nanosphere with ultra-thin wrinkled shell: Synergistic trapping of sulfur in Lithium-Sulfur batteries with excellent elasticity and buffer capability. (1st May 2018) - Liu, Ye; Yan, Wenjun; An, Xiaowei; Du, Xiao; Wang, Zhongde; Fan, Huiling; Liu, Shibin; Hao, Xiaogang; Guan, Guoqing
Abstract: To suppress the shuttle effect, reduce the capacity fade, and improve coulombic efficiency of Lithium-Sulfur (Li-S) battery, a polypyrrole hollow nanosphere (PHNS) with an ultra-thin wrinkled shell, which is expected to synergistically trap sulfur (S) with excellent elasticity and buffer capability, is fabricated by an in situ polymerization method. When S is encapsulated in PHNS (S@PHNS) with an optimum shell structure and used as the cathode, surprisingly, a specific capacity as high as 1500.5 mA h·g -1 in the first discharge at a current rate of 0.1 C with high coulombic efficiency as well as excellent rate performance is achieved. Also, a reversible capacity as high as 536.5 mA h·g -1 is obtained even at a high current rate of 5 C. Such a PHNS with the ultra-thin wrinkled shell has good conductivity, short ion and electron transport channel, and fast kinetics characteristics and especially during the charge-discharge cycles, it is conducive to the access of electrolyte and effective accommodation of the volume change. This PHNS should be a promising alternative cathode material for lithium-Sulfur batteries. Graphical abstract: Highlights: A hollow PPy nanosphere with ultra-thin wrinkled shell was fabricated for S trapping. The obtained hollow nanospheres had excellent elasticity and buffer capability. Synergistic confinement of S in hollow nanosphere for Li-S battery was confirmed. The obtained materials showed high cycling performance and rate capability.